Resistance of microbial community and its functional sensitivity in the rhizosphere hotspots to drought. (October 2021) - Zhang, Xuechen; Myrold, David D.; Shi, Lingling; Kuzyakov, Yakov; Dai, Hongcui; Thu Hoang, Duyen Thi; Dippold, Michaela A.; Meng, Xiangtian; Song, Xiaona; Li, Ziyan; Zhou, Jie; Razavi, Bahar S.
Abstract: Climate change impacts soil microbial communities, activities and functionality. Nonetheless, responses of the microbiome in soil microenvironments with contrasting substrate availability in the rhizosphere to climatic stresses such as drought are largely unknown. To fill this knowledge gap, we coupled soil zymography with site-specific micro-sampling of the soil and subsequent high-throughput sequencing. This helped identify how the bacterial community structure and the genes encoding N-cycling enzymes (leucine aminopeptidase and chitinase) in rhizosphere hotspots and coldspots (microsites with activities in the range of bulk soil but localized within the rhizosphere) of maize respond to drought (20% WHC, two weeks). The elevated activities of leucine aminopeptidase and chitinase in rhizosphere hotspots were caused by the tight collaborative relationships between bacteria and their stable network structure rather than by any significant shift in bacterial community structure or enzyme-encoding gene copies. Despite the similarity in bacterial community structure in soil under drought and optimal moisture, functional predictions indicated the increased relative abundance of genera belonging to Actinobacteria capable of leucine aminopeptidase and chitinase production, especially Streptomyces, Nocardioides, Marmoricola, and Knoellia . Accordingly, the number of gene copies encoded by Actinobacteria for these two enzymes increased by 5.0–17% under drought. Among the bacteria with increased relative abundance under drought, Luedemannella played a crucial role in mediating nutrients and energy fluxes between bacteria. This was reflected in a 35–70% increase in leucine aminopeptidase and chitinase activities under drought. The resistance of enzyme activities to drought was higher in hotpots than that in coldspots. These results revealed that rhizosphere bacterial community composition remained stable, and that the number of gene copies encoded by Actinobacteria responsible for N-cycling enzymes increased under drought. The expected reduction of processes of N cycle was absent. Instead, bacteria increased N mining rate in those hotspots remaining active despite water scarcity. Graphical abstract: Image 1 Highlights: Soil zymography is combined with high-throughput sequencing "Rhizosphere enzymatic coldspots" is for the first time localized Enzyme activity in hotspots was more resistant than that in coldspots to drought Bacterial community composition was stable between rhizosphere hot- and coldspots Enzyme-related genes encoded by bacteria were affected by drought